DNA Microarray Analysis of the Heat Shock Transcriptome of the Obligate Intracytoplasmic Pathogen Rickettsia prowazekii - Audia, Jonathon P. (American Society for Microbiology (ASM), 2008)
Here we present the first oligonucleotide DNA microarray analysis of global gene expression changes in the obligate intracytoplasmic pathogen Rickettsia prowazekii using temperature upshift as a model stress condition, and we describe a methodology for isolating highly purified rickettsial RNA. In toto, 23 transcripts were significantly increased by temperature upshift (≥2.0-fold; P < 0.05), and no transcripts demonstrated reproducible decreases. Array results for three heat shock-inducible mRNAs were confirmed using quantitative reverse transcription-PCR.